Weis-Fogh Mechanism Mathematic Model of Wave Power Generation Device - Chen, Xin; Kuang, Quan; Li, Yang; Wang, Songbo; Ye, Yunling; Zhang, Shesheng (Scientific Research, 2014)
A Weis-Fogh mechanism wave power generation system is designed, its physical model and mathematical model are discussed, and the component expressions of fluid dynamic expression are derived. Adopting numerical integral algorithm, the work done by fluid force acting on wing is calculated.
Keywords: Wave; Weis-Fogh; Power Generation; Mathematical Model